2019
DOI: 10.1002/aenm.201970117
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐Ion Batteries: 1T′‐ReS2 Confined in 2D‐Honeycombed Carbon Nanosheets as New Anode Materials for High‐Performance Sodium‐Ion Batteries (Adv. Energy Mater. 30/2019)

Abstract: In article number 1901146, Naiqin Zhao, Shi‐Zhang Qiao and co‐workers confine 1T'‐ReS2 in 2D‐honeycombed carbon nanosheets for sodium‐ion battery anodes. The intended 2D‐honeycombed carbon protective layer and the strong interfacial interaction contribute to the ultra‐stable long‐term cycling and high rate performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The findings showed that Re and carbon atoms donate charges to oxygen and that they are positively charged. [ 37,46,47 ] These findings confirm that V s ‐ReS 2 favorably impacts chemisorption and activation of CO 2 and electron transfer between CO 2 and V s ‐ReS 2 .…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The findings showed that Re and carbon atoms donate charges to oxygen and that they are positively charged. [ 37,46,47 ] These findings confirm that V s ‐ReS 2 favorably impacts chemisorption and activation of CO 2 and electron transfer between CO 2 and V s ‐ReS 2 .…”
Section: Resultssupporting
confidence: 57%
“…[ 30 ] As a new type of TMDs, ReS 2 has been studied in photocatalytic hydrogen evolution (PHE), both experimentally and theoretically. [ 31–38 ] Zhang et al [ 34 ] reported that ReS 2 exhibited significant performance in PHE, a two‐electron catalytic reaction. This is because free electrons are captured by tightly bound excitons to form trions that constrain recombination and thereby promote performance.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular carbon precursor, dopamine (DA), is ideal for adhering to various surfaces and self-polymerizing, without harming the original substrates. [107][108][109] The appropriate alkaline conditions and the moderate stirring speed are important to the polymerization of DA. The thickness of carbon coating layers can be modified by adjusting the concentration of DA monomers and the reaction time.…”
Section: Interfacial Doping Engineeringmentioning
confidence: 99%
“…In addition, the frequently used polyvinylidene fluoride (PVDF) polymer binder in the preparation of the electrodes can increase the resistance and obstruct active sites, and thus lead to capacity fading, especially at high current density. To resolve these issues, the most common strategy is encapsulation of the cobaltbased sulfide in highly electrically conductive carbon materials, such as porous carbon [85][86][87], carbon nanofibers [88][89][90], carbon nanotubes (CNTs) [91][92][93][94][95] and graphene [96][97][98]. The formed carbon-containing composites could shorten the Na + diffusion length, prevent the aggregation of nanocrystals, facilitate the surface pseudocapacitive process, and mitigate the volume variation in the Na + intercalation/deintercalation procedure.…”
Section: Carbon Based Materials Modificationmentioning
confidence: 99%